Intensifying great power politics in the Arctic - points for consideration by the kingdom of Denmark: From an analysis of assessments and strategies in Finland, Norway and Iceland - Mikkel Runge Olesen; Camilla Tenna Nørup (Danish Institute for International Studies (DIIS), 2019)
Great power politics in the Arctic are intensifying. The US, Russia and China are all strengthening their presence in the region. With the Arctic strategy of the Kingdom of Denmark presently in the process of being updated, this report analyses the assessments and strategies of Finland, Norway and Iceland and identifies points for consideration by the Kingdom of Denmark. These include emphasizing the value of closely coordinating with the other Nordic countries to establish Arctic-specific military confidence-building measures (CBMs); prioritizing the development of sufficient national capability to decrease reliance on immediate US and NATO involvement; taking a proactive approach to securing influence over the evolving military presence and activities of the US and NATO on the Kingdom of Denmark's territory; further exploring the idea of alternative funding options for Arctic development; and strengthening of Nordic collaboration on intelligence activities, information exchange and diplomatic efforts concerning all three great powers.
Keywords: 300; Geopolitik; Internationale Zusammenarbeit; Nordeuropa; Arktis; Dänemark; Finnland; Island; Norwegen; China; Russland; USA